A Middle Permian Ophiolitic Mélange Belt in the Solonker Suture Zone, Western Inner Mongolia, China: Implications for the Evolution of the Paleo‐Asian Ocean. Issue 5 (9th May 2018) - Fu, Dong; Huang, Bo; Kusky, Timothy M.; Li, Gangzhu; Wilde, Simon A.; Zhou, Wenxiao; Yu, Yang
Abstract: The Solonker suture zone in the southeastern Central Asian Orogenic Belt is generally regarded as the location of the final closure of the Paleo‐Asian Ocean, formed by complex and cryptic accretionary processes during late Paleozoic to early Mesozoic times. We recognize three tectonically juxtaposed lithotectonic units, including forearc basin sedimentary sequences, ophiolitic fragments, and ophiolitic mélange in the Solonker area, and here investigate the structural and kinematic features of the ophiolitic mélange in detail. The Solonker ophiolitic mélange has typical block‐in‐matrix fabrics with variably sized basalt, chert, sandstone, and ultramafic blocks embedded in siliceous‐argillaceous and siltstone matrices. Both extensional and contractional structures are well developed within the mélange, characterized by pervasive foliation, pinch‐and‐swell, boudinage, and S‐C fabrics. Kinematic analysis of the deformation structures indicates top‐to‐the‐N thrusting, correlated with the southward subduction of the southern margin of the Paleo‐Asian Ocean. Zircon U‐Pb ages of the matrices and a tonalite pluton intruded into the mélange constrain the formation age of the Solonker ophiolitic mélange to be middle Permian (ca. 268–260 Ma). Geochemical data from the ophiolitic rocks show subduction‐related characteristics with enriched large ion lithophile elements and depleted Nb, implying formation in a forearc setting. Our study provides robust evidence for the closure time of the Paleo‐Asian Ocean after the middle Permian. The late‐stage evolution of the Paleo‐Asian Ocean was characterized by subduction, forearc accretion with subsequent obduction of the kilometer‐scale upper plate, and soft collision, ultimately leading to the formation of the Solonker suture zone in the North China‐Mongolia segment. Key Points: Middle Permian ophiolitic mélange was documented from the Solonker area in the type locality of the Solonker suture zone Forearc basin sequence, upper plate fragment, and ophiolitic mélange units were tectonically juxtaposed by southward subduction Final closure of the Paleo‐Asian Ocean led to the formation of the Solonker suture zone after the middle Permian